Inhaled bronchodilators and the risk of tachyarrhythmias. (1st July 2015) - Lee, Chang-Hoon; Choi, Seongmi; Jang, Eun Jin; Yang, Han-Mo; Yoon, Ho Il; Kim, Yun Jung; Kim, Jimin; Yim, Jae-Joon; Kim, Deog Kyeom
Abstract: Background/objectives: There have been controversies about whether inhaled bronchodilators could increase the risk of clinically important tachyarrhythmias. We investigated the association between inhaled bronchodilators and the development of tachyarrhythmias, including atrial fibrillation and other paroxysmal tachyarrhythmias in real practice. Methods: We conducted a nested case–control study with the use of the nationwide insurance claims database of the Health Insurance Review and Assessment Service (Seoul, Republic of Korea). Overall, 3312 cases with newly developed tachyarrhythmias including atrial fibrillation and other paroxysmal tachyarrhythmias and 9732 matched (up to 1:5) controls were identified from 545, 508 subjects without acute major cardiovascular events in the past year between January 1, 2011 and December 31, 2011. Conditional logistic regression analysis adjusted by comorbidities, cardiovascular drugs and healthcare utilization was performed. Results: In various multivariate models, the use of inhaled long-acting muscarinic antagonists (LAMAs) or long-acting inhaled β2 agonists (LABAs) was significantly associated with tachyarrhythmias. Statistically significant effects of LAMAs on tachyarrhythmias were found only in the non-users of β-blockers. We did not find a statistically significant difference in the impact of a LABA without a LAMA vs a LAMA without a LABA (aOR, 0.93; 95% CI, 0.74–1.18), or a multiplicative or additive interaction between a LABA and a LAMA. Conclusions: Inhaled LAMAs and LABAs were significantly and comparably associated with an increased risk of tachyarrhythmias. Highlights: Inhaled LABA or LAMA was significantly associated with tachyarrhythmias. LAMA increased tachyarrhythmias in non-users of β-blockers. There was no multiplicative or additive interaction between LABA and LAMA.